Shotgun proteomics approaches for authentication, biological analyses, and allergen detection in feed and food-grade insect species. (July 2022) - Varunjikar, Madhushri S.; Belghit, Ikram; Gjerde, Jennifer; Palmblad, Magnus; Oveland, Eystein; Rasinger, Josef D.
Abstract: Untargeted proteomics can contribute to composition and authenticity analyses of highly processed mixed food and feed products. Here, we present the setup of an analytical flow tandem mass spectrometry method (AF-HPLC HR-MS) for analysis of insect meal from five different species. Data acquired were compared with previously published data employing spectra matching and standard bottom-up proteomics bioinformatics analyses. In addition, data were screened for insect species marker peptides and common allergens, respectively. The results obtained indicate that the performance of the newly established AF-HPLC HR-MS workflow is in line with previously published methods for insect species differentiation. Data obtained in the present study, also lead to the discovery of novel markers for the development of targeted MS analyses of insect species in food- and feed-mixes and highlighted that known allergen such as arginine kinase or tropomyosin were consistently detected across all five species tested. Graphical abstract: Image 1 Highlights: Normal flow proteomics workflow developed for food and feed safety research. Proteomics profiles of five insect species was analysed and reported. QTOF and HR-MS spectral libraries for insect species authentication created. Food allergens detected in the collected insect data.